"Cultural turns" as a request for culturology - O. V. Shynkarenko (Ukrainian Cultural Studies, 2018)
The article analyzes the phenomenon of the "cultural turn" in a series of fixed methodological turns in the social and humanitarian knowledge of the last decades. Appeal to this trend in different research fields makes it possible to discover the cultural direction of scientific search, which can be linked to the emergence of a special subject area of culturology. In turn, the emerging cultural research in its domestic experience is difficult to determine with the specifics of its research task. Moreover, it was the "cultural turn" in the social and humanitarian sphere in the West that was realized by its own research project. "Cultural studies" (the Birmingham (UK) Centre for Contemporary Cultural Studies or The Birmingham School), which is an interdisciplinary research area that includes feminism, poststructuralism, post-modernism, post-colonialism, aspects of Marxism and humanism in the study of the process of creating values, values, identities. Difficulties in culturology self-determination of their theoretical originality in the study of culture in the context of the culture-centeredness of various subjectmatter branches do not reduce, but, on the contrary, increase its research potential for an integral examination of culture. However, the success of the scientific contribution of culturology in understanding the primary importance of culture in sociocultural processes is seen in the productive use of culture achieved in subject-oriented social analysis as diverse practices. Thus, culturology joins those studies that today increasingly pay attention to "practices" as a field in which it seeks a solution of pressing anthropological and socio-cultural problems. Today’s request for an understanding of social processes, which in its complexity, the more so, does not fit into a predetermined human dimension, actualize a review of the understanding of society in the light of living human interaction. Then the multilayeredness, the diversity of the phenomenon of culture, the awareness of its various types will contribute to the discovery of culture as a living life of people fixed in living experience, defining it as a situationally manifested meaningful order of action.